PENGEMBANGAN BAHAN AJAR BERMUATAN BUDI PEKERTI PADA PEMBELAJARAN MENULIS CERPEN UNTUK SISWA KELAS IX - Wismanto, Agus (SASINDO, 2013)
The problems in this research is the development of teaching material for writing short stories containing ethical themes for students of class IX. The subproblemsare divided into: (1) how is the extent of learning characteristic ofwriting short stories containing ethical themes for students of class IX, (2) how isthe development of writing short stories containing ethical themes for students ofclass IX, (3) how is the effectiveness of learning material for writing short storiescontaining ethical themes for students of class IX. The purposes of this researchare: (1) to decribe the characteristics of short stories on the subject of writingshort stories containing ethical themes for students of class IX, (2) to develop thecharacteristics of short stories on the subject of writing short stories containingethical themes for students of class IX, (3) determine the effectiveness of teachingmaterial on the subject of writing short stories containing ethical themes forstudents of class IXThis study used research and development approach by applying a tenstepimplementation, referring to the theory of Borg and Gall (2002:571) whichare summarized into seven steps.Based on the research analysis and discussion, it is summarized into someconclusions; (1) a description of short stories characteristics in learning writingshort stories containing ethical values for IX grade students, which includes (a) adescription of short stories characteristics based on the short stories conditions,(b) a description of short stories characteristics based on the theme, setting, plot,characters, and the types of short stories, (c) a description of teaching materialscharacteristics in writing short stories is based on the bookâs cover like the shape,the size, and thickness of books. (d) a description of teaching materialscharacteristics in writing short stories is based on the language used in the book.(e) while in the supporting aspect.Key words: Improvement of teaching, writing short stories, character building.